Chapter 7 Gender-Based Violence and the Performance of Masculinity A Comparative Analysis of the Documentary Films Ma l'amore c'entra? and Serás hombre - Calderón Sandoval, Orianna (Taylor & Francis, 2022)
The aim of this chapter is to analyse how two documentary films, Elisabetta Lodoli's Ma l'amore c'entra? and Isabel de Ocampo's Serás Hombre, critically explore the interrelation between the performance of hegemonic masculinities and gender-based violence. Our methodology focuses on the affective and performative dimensions of documentary cinema since we look for ways in which emotions work in and through gender-based violence, shaping performances of masculinity. We also identify 'moments of affection', where possibilities of transformation can be envisioned. The chapter is divided into four sections. The first provides the theoretical framework, which combines feminist critiques of how gender-based violence is represented in mainstream media, the intersections between the exercise of violence and the performance of masculinity, and a description of what a performative and affective approach to the analysis of documentary cinema entails. The second and third sections present the analysis of our case studies. With hate and anger as our entry points, we close-read selected scenes from each film, incorporating opinions expressed by their directors and reactions from spectators. We conclude by summarising the modes in which our case studies set into motion ways of performing cultures of gender equality on both sides of the camera and the screen.